Afghanistan and Pakistan’s Security Paradigm: Assessing Contemporary Risks and Strategic Realities - *Dr. Tahira Mumtaz; Amina Tahir (Journal of Social Signs Review, 2026)
This research analyzes Pakistan's security calculus, which has evolved under Afghanistan's influence, given the two states' shared history and border. Changes in Afghanistan also affect Pakistan's internal stability and security. The purpose of this study is to understand how Afghanistan's instability shapes Pakistan's security priorities and national interests. The study used a qualitative research method that was based on research articles, official documents, books, and reports. Pakistan's security environment and developments in Afghanistan are examined in an analytical and descriptive study. The theoretical framework of this research focused on the historical causes behind the conflict of Afghanistan and Pakistan, such as military operations, the impact of refugees, and terrorism threats. It focused on the facilitation of cross-border management, long-term planning, and security-oriented factors. It highlighted the major Soviet invasion and its impact on the security of Pakistan and Afghanistan. Findings of the research show that militant groups and terrorism became major threats to Pakistan after 1990. They attacked inside Pakistan and targeted civilians, institutions, and schools. Afghan refugees arrived in Pakistan, increased demand for hospitals, schools, jobs, and housing, and put pressure on the economy of Pakistan. In addition, the research reviews policies of Pakistan towards Afghanistan to control militancy through intelligence coordination, military operations, and border fencing. It helps to reduce terrorist attacks and militancy in areas they attacked, but regional cooperation and peace require long-term policies, political stability, and economic progress. The study concludes that Pakistan's security is strongly influenced by Afghanistan, through border challenges, terrorism, and refugee pressure. Peaceful Afghanistan and Pakistan's balanced strategic policies can create regional and trade opportunities for both states. Keywords: Militancy, Security, Terrorism, Borders, Stability, Protection, Insurgency.